Effect of tungsten carbide addition on the tribological behavior of Astaloy 85Mo powder consolidated via spark plasma sintering. (November 2018) - Ordoñez, M.F.C.; Farias, M.C.M.; Machado, I.F.; Souza, R.M.
Abstract: Hard particle addition in ferrous powders allows the production of sintered materials with higher toughness, hardness and wear resistance, with potential use in different technological applications. This combination of properties is attained following correct mixture and sintering procedures that result in the formation of composites with low porosity and adequate particle distribution. In this work, Astaloy 85Mo ferrous powders were mixed with different tungsten carbide (WC) additions (2, 5, 7 and 10 wt%) by mechanical alloying (MA) and consolidated by spark plasma sintering (SPS), providing samples with higher real density, and without an increase in porosity (or apparent volume). SPS enhanced sinterability using low sintering time that reduces carbon diffusion from WC to the ferrous matrix. Tribological evaluation was conducted by means of ball-on-disk tests with different loads (5, 10, 15 and 20 N). Specimens were in contact with an AISI 52100 ball with a diameter equal to 10 mm and the friction and wear coefficient of both bodies in contact were reported. Results indicated that WC addition contributed to load support and decrease of matrix plastic deformation. Additions higher than 7 wt% of WC, in conditions of high normal load, resulted in the detachment of WC particles and abrasive wear of the counterpart. Highligths: Addition of WC carbide reduces the adhesive wear in low-carbon Astaloy 85Mo sintered steel. WC carbides network contributes with load support and reduction of plastic deformation of steel matrix. Ball milling route enhances the consolidation of ceramic-metallic powder mixtures with different starting properties. Higher WC addition increase the composite hardness but excess of particles can promote particles detachment and abrasion.